Intelligent Medical Diagnostic Assistant ˜Deep Learning for Skin Cancer Detection - Mallek Haddad; Mallek Djoudi (My University, 2025)
Skin cancer is a significant public health issue where early detection is crucial. Deep learning offers promising avenues for the automated diagnosis of cutaneous lesions. This study focuses on the design and evaluation of hybrid deep learning architectures to enhance detection performance. Four distinct models were proposed and analyzed: Hybrid ResNet50-Vision Transformer (ViT), ResNet50-EfficientNet, ResNet50-Swin Transformer, and an architecture combining ViT and its optimized variant, Stepwise ViT. These models were trained and validated on the public HAM10000 dataset, after a class balancing procedure. Experimental results demonstrated the efficacy of hybrid approaches, with the ResNet50-Swin Transformer model exhibiting superior performance based on evaluation metrics. This research confirms the significant potential of hybrid deep learning models for analyzin dermatological images and opens avenues for developing more precise and dependable clinical decision support tools. ----------------------------------------------------------------------- يمثل سرطان الجلد تحديا كبيرا للصحة العامة، ويعد الكشف المبكر عنه أمرًا بالغ الأهمية. يقدم التعلم العميق آفاقا واعدة للتشخيص الآلي للآفات الجلدية. تركز هذه الدراسة على تصميم وتقييم معماريات تعلم عميق هجينة لتحسين أداء الكشف. ثم اقتراح وتحليل أربعة نماذج متميزة - Hybrid ResNet50 ResNet50-Efficient Net, Vision Transformer (ViT) ونسخته المحسنة VIT ومعمارية تجمع بين ،ResNet50-Swin Transformer, .Stepwise Vit تم تدريب هذه النماذج والتحقق من صحتها على مجموعة البيانات. العامة 10000 HAM ، بعد إجراء موازنة للفئات. أظهرت النتائج التجريبية فعالية النهج الهجينة، حيث أظهر نموذج ResNet 50-Swin Transformer | أداء متفوقا بناءً على مقاييس التقييم. يؤكد هذا البحث الإمكانات الكبيرة النماذج التعلم العميق الهجينة في تحليل الصور الجلدية، ويفتح آفاقا لتطوير أدوات دعم قرار سريري أكثر دقة وموثوقية ----------------------------------------------------------------------- Le cancer cutané représente un enjeu majeur en santé publique, nécessitant une détection précoce. Le domaine du deep learning présente des perspectives prometteuses en ce qui con-cerne le diagnostic automatisé des lésions cutanées. L’objet de cette étude concerne la concep-tion et l’évaluation d’architectures hybrides de deep learning en vue d’améliorer la détection. Quatre modèles distincts ont été proposés et analysés : Hybrid ResNet50-Vision Transformer (ViT), ResNet50-EfficientNet, ResNet50-Swin Transformer, ainsi qu’une architecture combinant ViT et sa variante optimisée, Stepwise ViT. Ces modèles ont été entraînés et validés sur le jeu de données public HAM10000, après une phase d’équilibrage des classes. Les résultats expérimentaux ont démontré l’efficacité des approches hybrides, le modèle ResNet50-Swin Transformer se distinguant par des performances supérieures en termes de métriques d’évaluation. Ces travaux confirment le potentiel significatif des modèles hybrides d’apprentissage profond pour l’analyse d’images dermatologiques et ouvrent la voie au développement d’outils d’aide au diagnostic clinique plus précis et fiables.
Keywords: Skin cancer; Medical imaging; Deep learning; Automated detection; Hybrid mod- els; ResNet50; Vision Transformer (ViT); EfficientNet; Swin Transformer; HAM10000; سرطان الجلد التصوير الطبي التعلم العميق، الكشف الآلي Vision Transformer (VIT) ResNet50 النماذج الهجينة HAM10000. Swin Transformer Efficient Net; Cancer de la peau; Imagerie médicale; Apprentissage profond; Détection automa-tisée; Modèles hybrides